Predicting first-trimester outcome of embryos with cardiac activity in women with recurrent spontaneous abortion - Huixian Li; Shuang Qin; Fanfan Xiao; Yuhong Li; Yunhe Gao; Jiexin Zhang; Qing Xiao (Journal of International Medical Research, 2020)
Objective This study was performed to evaluate the capability of routine clinical indicators to predict the early outcome of embryos with cardiac activity in women with recurrent spontaneous abortion (RSA). Methods A retrospective cohort study of pregnant women with a history of RSA in a Chinese tertiary hospital was performed using unadjusted and multivariable logistic regression. Results Of 789 pregnant women with RSA, 625 (79.21%) had ongoing pregnancy, whereas 164 (20.79%) developed abortion before 20 full weeks of gestational age even after embryonic heart motion was detected. The final model had an area under the curve of 0.81 (95% confidence interval, 0.78–0.84) with a sensitivity of 74.39%, a specificity of 76.00%, and a false-positive rate of 52.32% at a fixed detection rate of 90%. Conclusions The combination of multiple routine clinical indicators was valuable in predicting the early outcome of embryos with cardiac activity in viable pregnancies with RSA. However, this model might result in a high false-positive rate with a fixed detection rate of 90%; other markers must be investigated to identify first-trimester RSA once positive embryonic heart motion is established.